A new species of deep-sea Tegastidae (Crustacea: Copepoda: Harpacticoida)from 9°50´N on the East Pacific Rise, with remarks on its ecology - Gollner, Sabine; Ivanenko, Viatcheslav N.; Arbizu, Pedro Martinez (Zootaxa, 2008)
Both male and female of the new deep-sea species Smacigastes barti sp. nov. (Tegastidae, Sars) are described in detail. Copepoda is one of the most diversified taxa at deep-sea hydrothermal vents, but only one species of the family Tegastidae has been described from this habitat and other deep-sea environments. Smacigastes barti is the second species of the genus Smacigastes Ivanenko & Defaye, 2004, and was found in artificial substrates deployed in the vicinity of and 0.5 m from tubeworm aggregations at the 9°50´N region on the East Pacific Rise at 2500 meters depth. The derived character states of the new species are the lack of coxal endites on the maxilla, and 2-segmented exopods of swimming legs 2 and 3, the latter being the result of the fusion of the 2 proximal segments. An identification key to all known genera of Tegastidae is provided. Interestingly, the distribution of S. barti showed that it does not tolerate elevated temperatures and/or the presence of hydrogen sulfide or oxygen fluctuations, although both species of this genus were found in deepsea chemosynthetic environments.